Bi-level coordinated restoration for the distribution system and multi-microgrids - Hao Zhu; Xiaotian Sun; Haipeng Xie; Lingfeng Tang; Zhaohong Bie (International Journal of Electrical Power & Energy Systems)
Microgrids (MGs) play an important role in enhancing the resilience of distribution systems (DSs). However, each MG has its own operation scheme and the ownership obstructs the coordination of restoration resources from different MGs. To address this problem, this paper proposes a bi-level coordinated restoration framework for the distribution system operators (DSOs) and the microgrid operators (MGOs). In the framework, MGOs report their surplus capacity to DSO once an extreme event occurs, and then DSO dispatches its own resources and orders MGOs’ supporting capacity. After receiving the order, MGOs dispatch distributed generators and energy storage systems to provide the surplus power. The proposed framework is capable of finding the optimal restoration scheme provided that the autonomy of MGs is retained. The stochastic programming is leveraged to model the uncertainty of renewable energy, and the coordinated restoration framework is formulated as a bi-level mixed integer linear programming (BMILP). The relaxation-based bi-level reformulation and decomposition (RBRD) algorithm is adopted to effectively achieve the global optimal solution. The effectiveness of the proposed method is validated on a test system comprised of the IEEE 33-bus system and three IEEE 13 node test feeders.